Variation of Adolescent Snack Food Choices and Preferences along a Continuum of Processing Levels: The Case of Apples - Elizabeth Svisco; Carmen Byker Shanks; Selena Ahmed; Katie Bark (Foods, 2019)
Food processing is used for transforming whole food ingredients into food commodities or edible products. The level of food processing occurs along a continuum from unprocessed to minimally processed, processed, and ultra-processed. Unprocessed foods use little to no processing and have zero additives. Minimally processed foods use finite processing techniques, including drying, freezing, etc., to make whole food ingredients more edible. Processed foods combine culinary ingredients with whole foods using processing and preservation techniques. Ultra-processed foods are manufactured using limited whole food ingredients and a large number of additives. Ultra-processed snack foods are increasing in food environments globally with detrimental implications for human health. This research characterizes the choices, consumption, and taste preferences of adolescents who were offered apple snack food items that varied along a processing level continuum (unprocessed, minimally processed, processed, and ultra-processed). A cross-sectional study was implemented in four elementary school classrooms utilizing a buffet of apple snack food items from the aforementioned four food processing categories. A survey was administered to measure students’ taste acceptance of the snacks. The study found that the students selected significantly (p < 0.0001) greater quantities of ultra-processed snack foods (M = 2.20 servings, SD = 1.23) compared to minimally processed (M = 0.56 servings, SD = 0.43) and unprocessed (M = 0.70 servings, SD = 0.37) snack foods. The students enjoyed the taste of ultra-processed snack foods (M = 2.72, SD = 0.66) significantly more (p < 0.0001) than minimally processed (M = 1.92, SD = 1.0) and unprocessed (M = 2.32, SD = 0.9) snack foods. A linear relationship was found between the selection and consumption quantities for each snack food item (R2 = 0.88). In conclusion, it was found that as processing levels increase in apple snack foods, they become more appealing and more heavily consumed by elementary school students. If applied broadly to snack foods, this conclusion presents one possible explanation regarding the high level of diet-related diseases and nutrient deficiencies across adolescents in America. Food and nutrition education, food product development, and marketing efforts are called upon to improve adolescent food choices and make less-processed snack food options more appealing and accessible to diverse consumers.